AS CONCEPÇÕES DE HISTÓRIA E OS CURSOS DE LICENCIATURA (Revista de História Regional, 2007)
This paper discusses problems around the insuficcient concepts - mainly the ones related to the positivism - in the debates about the teaching of history where it is argued that this situation is a symptom of insuficient theoretical formation and academic debats about historiographic tendencies in producing the maintenance of regular problems in the teaching of history.